Влияние социальных сетей на формирование массового политического сознания - Нехаенко, Оксана Васильевна; Нехаєнко, Оксана Василівна; Nekhaienko, Oksana V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Обосновывается необходимость изучения политического сознания через средства массовой коммуникации как главного транслятора государственных идеологий, оказывающего значительное воздействие на политическое сознание, в первую очередь посредством знаков и символов. С целью определения факторов такого влияния проводится дискурс-анализ двух социальных сетей. Установлено, что используемые механизмы влияния и технические приёмы противоборствующих политических сил и направлений зачастую практически тождественны. The paper concerns political consciousness as a specific type of consciousness, its essence and close connection with political processes and phenomena. The term “political consciousness” is defined. It is stated that political consciousness should be studied in the framework of mass media as they present the main translator of state ideologies. Mass media are the most powerful means of influence on public consciousness. Such influence is exercised firstly through signs and symbols. The objective of the article is to point out the factors influencing mass consciousness and to determine which specificities are characteristic of consciousness in societies experiencing the state of crisis. In order to solve the set tasks quality methods and exactly discourse-analysis were used. We can state that the specificity of modern mass media is the idea of individualism and free choice of information sources but practically mass media and social nets present the arena where the struggle between political forces takes place. Social networks is an arena for confrontation between political forces and trends, regardless of their content aspect, the impact of the mechanisms used and the technical methods are practically identical. Social networks occupy a dominant position among the QMS, which makes it possible to say that today many social networks define the entire spectrum of public opinion, the differences in positions. Sometimes civil administration is carried out with their help.
The Impact of Social Networks on the Formation of Mass Political Consciousness
Keywords: политическое сознание; социальные сети; идеология; социальный контроль; символическое измерение реальности; political consciousness; social networks; ideology; social control; symbolical change of reality